Carabid beetles (Coleoptera: Carabidae) from the upper course of the Neretva River in Bosnia and Herzegovina - Wolfgang Paill; Johanna Gunczy (Natura Sloveniae)
During a four-day collection period, 89 ground beetle species were found in the upper course of the Neretva valley near Ulog. Many of them are classified as riparian floodplain specialists. A large proportion of these species, such as Bembidion conforme, have their main distribution in Central Europe, but are very rare in the Balkans. Consequently, these findings form important arguments revealing the upper Neretva to be of high importance in terms of nature conservation.